Industri UMKM dan E-Commerce pada Teknologi di Indonesia - Tohonan Rohani Silaban; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to increase knowledge and insight in the field of industrial economics and aims to analyze industrial competitive strategies in facing technological advances. The research method uses qualitative methods and library research. The data collection technique is to record important information in carrying out data analysis by means of data reduction, data presentation and drawing conclusions to obtain conclusions. The research results show that the MSME and E-Commerce industries are able to survive in competition by using increasingly advanced technology and production will increase. increasing in meeting the needs of society, increasing growth as well as global market demand, although industry can be one of the strategies in the industrial sector that can be developed in the future in an effort to realize Indonesia's economic growth.